Effect of pre-operative radiation therapy on surgical outcome in retroperitoneal sarcoma - Sung Jun Jo; Sean S. W. Park; Gyu Sang Yoo; Kyeong Deok Kim; So Hee Lim; Jinseob Kim; Min Jung Kim; Jeong Il Yu; Jae Berm Park; Kyo Won Lee (Frontiers in Surgery, 2023)
BackgroundA high rate of locoregional recurrence is one of the major difficulties in successful treatment of retroperitoneal sarcoma (RPS). Although pre-operative radiation therapy (RT) is considered a potential way to improve local recurrence, concerns about the associated treatment toxicity and risk of peri-operative complications need to be addressed. Hence, this study investigates the safety of pre-operative RT (preRTx) for RPS.MethodsA cohort of 198 patients with RPS who had undergone both surgery and RT was analyzed for peri-operative complications. They were divided into three groups according to the RT scheme: (1) preRTx group, (2) post-operative RT without tissue expander, and (3) post-operative RT with tissue expander.ResultsThe preRTx was overall well tolerated and did not affect the R2 resection rate, operative time, and severe post-operative complications. However, the preRTx group was associated with higher incidence of post-operative transfusion and admission to intensive care unit (p = 0.013 and p = 0.036, respectively), where preRTx was an independent risk factor only for the post-operative transfusion (p = 0.009) in multivariate analysis. The median radiation dose was the highest in preRTx group, although no significant difference was demonstrated in overall survival and local recurrence rate.ConclusionThis study suggests that the preRTx does not add significant post-operative morbidity to the patients with RPS. In addition, radiation dose elevation is achievable with the pre-operative RT. However, a meticulous intra-operative bleeding control is recommended in those patients, and further high-quality trials are warranted to evaluate the long-term oncological outcomes.